Dynamic Policies to Over Come the Pressing Challenges in the Libyan Education System: Proactive Simulations within the Faculty of Education University of Benghazi (London Journal of Research In Humanities and Social Sciences, 2023)
This study is the result of long-term field investigations of the complications facing the Libyan education system (LES). This work included several deep research studies intended to measure different aspects of the LES; its categories of education, administrations, and contributors; and their associated problems. These studies, which occurred predominantly between 2019 and 2023, have clearly recognized that the LES’s inputs and output sface huge challenges which may quickly lead  to a definite collapse, unless all the current conflicting authorities take majoractions to ward a professional reform plan. Further more, these authorities may need to adapt immediate rescue measures, especially in terms of policies, supportive legislations, qualifiedleader ship, and strict employment of the quality and assurance functions. Elab bar first formulated a plan in 2017, which reached its final form in 2022, entitled “Reforming the Libyan Education System: Seven Articulated Years Via a Strategic Planning Pyramid”.Subsequently, Elabbar published two field studies: “Repercussions of the Continuous Instability for the Quality of Education in the State of Libya:  An Investigational Study within the Faculty of Education, University of Benghazi (UoB)” (2022) and” Implementing Recommendations at the Faculty of Education, University of Benghazi (UoB): Action Research Methods to Enhance the Desired Reform Strategy” (2023). These studies proposed to continue strengthening the reform proposal with further functional field studies to develop policiesfor different levels of education and launch practical procedures of the transformative models of Continuing Professional Development (CPD),as well as further experimental studies on the values of reform and the substantiality of CPD. This aims to revitalize the foundation of the reform strategy with further insights and practical reflections. Moreover, due to the deep impacts of the ongoingpolitical instabilityon the quality of the Libyaneducation; the obvious absence of any clear education policy among parliament; and conflicts within ministries of education, public universities, and even the schooling system, it seemsalmost impossible for the current authorities to launch gradual national reformprocedures (as suggested) in the near future. Therefore,this study seeks to continue examining the accomplished results andrecommendations and developing the reformstrategy, with particular focuses on the role of policies in education and the roles of faculties in education, as the first years of the reform strategyinvolvefoundational polices, advised legislations, and CPD programs to be applied for all stakeholders and policymakers who are in charge of leading thedesired national reform. This study utilizes the latestresearch’s (Elabbar, 2021, 2022, 2023) positive findings, insights, and experimentation results.All will bereproducedvia fourmodi fied innovative activities–policy, process, procedures, and props (4P’s) –to be examined by the Faculty of Education -UoB, five secondary schoolsinvolved inthe teaching practice program (practicum),and several types of stakeholders from different levels and positions within the LES. The research discovered more complications facing the LES and reached agreater understanding of the suitable transformative CPD modelto be added to the first two years of the reform plan. Additionally, the study developed dynamic policiesto join faculties of education with schooling systems in a preparationaltactic to enhance Elabbar’s (2022) planned seven gradual reform years with valuable, up-to-datestrategies.
Keywords: transformative model of CPD; designed academic reflation; dynamic policy plan from the Faculty of Education & practicum